Content Analysis Of Iranian Tourism Websites Based On Media Richness Theory - Saatsaz, Masoumeh (2009)
This research was conducted to examine media richness theory in the content of Iranian tourism websites. Eighty one Iranian tourism website with different tourism services formed the population which was obtained from KETABE AVAL directory within two weeks in December 2007. Due to the limited number of websites in the population, the researcher decided to analyze the whole of population, so a census was carried out. The researcher defined the richness factors based on the elements and techniques of a website design, and these techniques and elements were analyzed according to the frequency of use on the investigated websites. Hence, the content analysis technique was recognized as the most suitable method to conduct this research. For pretesting 20 websites were randomly selected and analyzed in order to refine codes. The results showed that the findings of the pre-test answer the research questions. The coded data were analyzed using Microsoft Excel 2003. The results of the analysis were presented in the form of cross tables containing frequencies and percentages for the different tourism services, which helped the researcher in discussing about (the conditions of) the tourism websites in Iran. The results yielded in the study and the discussions showed that although tourism websites in Iran mostly employed different feedback techniques (approximately 82.7%), only half of them made quick feedback to their customers (50.6%). In terms of multiplicity of cues and channels more than half (54.4%) of the websites did not applied various information channels to present their products and services. But they were moderately available in two languages (i.e. Farsi and English) by 60.5%. In addition, half of them were moderately readable and conversely only 17.4% of the websites were highly searchable (i.e. easy to navigate) in terms of personal focus factor. the researcher also put forward some suggestions for other researchers who wish to carry out similar studies in the future.